Observation of the suppressed Λ0b→DpK− decay with D→K+π− and measurement of its CP asymmetry - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review, 2021)
A study of Λ0b baryon decays to the DpK− final state is presented based on a proton-proton collision data sample corresponding to an integrated luminosity of 9 fb−1 collected with the LHCb detector. Two Λ0b decays are considered, Λ0b→DpK− with D→K−π+ and D→K+π−, where D represents a superposition of D0 and ¯D0 states. The latter process is expected to be suppressed relative to the former, and is observed for the first time. The ratio of branching fractions of the two decays is measured, and the CP asymmetry of the suppressed mode, which is sensitive to the Cabibbo-Kobayashi-Maskawa angle γ, is also reported.